Proceedings of the Eighth ACM SIGKDD International Conference on Knowledge Discovery and Data Mining 2002
DOI: 10.1145/775047.775090
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting unlabeled data in ensemble methods

Abstract: An adaptive semi-supervised ensemble method, ASSEM-BLE, is proposed that constructs classification ensembles based on both labeled and unlabeled data. ASSEMBLE alternates between assigning "pseudo-classes" to the unlabeled data using the existing ensemble and constructing the next base classifier using both the labeled and pseudolabeled data. Mathematically, this intuitive algorithm corresponds to maximizing the classification margin in hypothesis space as measured on both the labeled and unlabeled data. Unlik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(82 citation statements)
references
References 12 publications
1
79
0
2
Order By: Relevance
“…The pseudolabeled data is combined with the original labeled data and the classifier is trained again. The classifier we use is Discrete AdaBoost [4]. We will use this method as a baseline method in the experiments.…”
Section: Frame-level Labelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pseudolabeled data is combined with the original labeled data and the classifier is trained again. The classifier we use is Discrete AdaBoost [4]. We will use this method as a baseline method in the experiments.…”
Section: Frame-level Labelsmentioning
confidence: 99%
“…We will use this method as a baseline method in the experiments. This kind of self-training [14] procedure has been used extensively in different domains [10][17] and achieved top results in the NIPS competition [4].…”
Section: Frame-level Labelsmentioning
confidence: 99%
“…The learning process is a type of ensemble learning [9][10][11]. It involves multiple classifiers which label the unlabeled data to update and improve each other [12].…”
Section: Introductionmentioning
confidence: 99%
“…D´Alch´e Buc et al [2] showed that the error function can be extended and applied in the case of semi-supervised learning. K.P.Bennett [3] further proposed the ASSEMBLE algorithm, which works with any cost-sensitive base learner and at the same time has a simple, adaptive step-size rule. Although semi-supervised ensemble methods perform well in the empirical tests on both two-class and multi-class problems, they fail on complex dataset [2], where the labeled data will really bring crucial information that can't be obtained in unlabeled data such as the case in video dataset.…”
Section: Introductionmentioning
confidence: 99%
“…the unlabeled data can be assimilated into margin cost sensitive ensemble algorithms etc. [3]). Moreover, it takes advantages of active learning to accelerating the converging speed of the learning process.…”
Section: Introductionmentioning
confidence: 99%